1999
DOI: 10.1002/(sici)1097-4628(19991121)74:8<1881::aid-app1>3.0.co;2-5
|View full text |Cite
|
Sign up to set email alerts
|

Crosslinked poly(vinyl alcohol) supports for the immobilization of a lipolytic enzyme

Abstract: Different esters of crosslinked poly(vinyl alcohol) (PVA) were synthetized. They were developed for protein fractionation and immobilization. PVA was crosslinked with epichlorohydrin (CL-PVA) and esterified with linear fatty acids of different length (Cn-CL-PVA). A characterization of the obtained products was made. The swelling behavior, the solubility, and the percentage of esterification were examined. Values of equilibrium water content of about 81% were reached for CL-PVA samples. The polymers' stability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 15 publications
0
12
0
Order By: Relevance
“…18−21 Many heuristic studies have been undertaken aimed at probing adsorption-induced polymer surface structural changes at the molecular level, including the ordered alignment of liquid crystal molecules on rubbed polymer substrate surfaces, 22 formation of surface hydrogen bonds of poly(2-methoxyethyl acrylate) with water and bisphenol A, 5,23 and adsorption-induced orientational order changes of the phenyl groups at phenolic resin surfaces. 24 Because of their excellent biocompatibility, biodegradability, and water solubility properties, polyvinyl alcohol (PVA)-based materials have received considerable attention for application in many areas, such as environmentally safe products, 25 protein purification, 26 enzyme immobilization, 27 membrane separation, 28,29 and biomechanical applications. 30 In most of the applications above, spontaneous adsorption of various molecules is common on PVA surfaces, resulting in poor performance of the PVA materials.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…18−21 Many heuristic studies have been undertaken aimed at probing adsorption-induced polymer surface structural changes at the molecular level, including the ordered alignment of liquid crystal molecules on rubbed polymer substrate surfaces, 22 formation of surface hydrogen bonds of poly(2-methoxyethyl acrylate) with water and bisphenol A, 5,23 and adsorption-induced orientational order changes of the phenyl groups at phenolic resin surfaces. 24 Because of their excellent biocompatibility, biodegradability, and water solubility properties, polyvinyl alcohol (PVA)-based materials have received considerable attention for application in many areas, such as environmentally safe products, 25 protein purification, 26 enzyme immobilization, 27 membrane separation, 28,29 and biomechanical applications. 30 In most of the applications above, spontaneous adsorption of various molecules is common on PVA surfaces, resulting in poor performance of the PVA materials.…”
Section: Introductionmentioning
confidence: 99%
“…Because of their excellent biocompatibility, biodegradability, and water solubility properties, polyvinyl alcohol (PVA)-based materials have received considerable attention for application in many areas, such as environmentally safe products, protein purification, enzyme immobilization, membrane separation, , and biomechanical applications . In most of the applications above, spontaneous adsorption of various molecules is common on PVA surfaces, resulting in poor performance of the PVA materials.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, it is hydrophilic, it can be easily modified through its hydroxylic groups, and it is commercially available in a wide range of molecular weights at a low price. Therefore it is used in various cross-linked forms giving hydrogels or membranes to employ in protein purification and immobilization studies [6]. Several studies have been reported on the use of PVA for enzyme immobilization [7].…”
Section: Introductionmentioning
confidence: 99%
“…Poly(vinyl alcohol) (PVA), having water‐soluble, biodegradable, biocompatible, gas‐barrier, and high mechanical properties, is attractive for environmentally friendly products, medical applications, protein purification, enzyme immobilization, and membrane preparation 6–14. More recently, PVA‐based nanocomposites have been developed to improve PVA's properties and further explore its applications 15–17.…”
Section: Introductionmentioning
confidence: 99%